Lexical Relation in the Coldplay’s Album “A Head Full of Dream” - Kevin Yvonnaha Harefa; Arsen Nahum Pasaribu (Edu-Ling: Journal of English Education and Linguistics, 2023)
The goal of this research is to reveal the various types of lexical relation realized in the song lyrics of Coldplay's album “A Head Full of Dream” and to interpret the meaning of lexical relation of song lyrics. Even though this research is similar to the object or theory with others, this research has made sure there are some differences such as the result and the idea being focused on Saeed's division. It examined the data in the text using the descriptive qualitative method. The data was song lyrics from Coldplay's album, which has nine songs. The information was compiled into a single song lyric. As a result, each word would be linked to the other words that have a relationship. Also, one lexical relation discovered would be listed in one song lyric. This investigation discovered the relations based on Saeed's idea, such as synonyms, antonyms, polysemy, homonym, hyponym, and meronyms. This study also concluded that synonym is more dominating relationship and meronym has fewest relations based on the data analysis.